2020
DOI: 10.1016/j.psj.2020.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chestnut wood extract on performance, meat quality, antioxidant status, immune function, and cholesterol metabolism in broilers

Abstract: Plant extracts have been proved as natural antioxidants resources as well as alternative feed additives in livestock and poultry species. Chestnut wood extract ( CWE ) as a source of hydrolysable tannic acid was used to evaluate the growth performance, nutrient retention, meat quality, antioxidant status, and immune function of broilers. A total of 168, day-old Arbor Acre male broilers (weight 46.59 ± 0.44 g) were randomly divided to 3 treatments, 7 replicate pens per treatment, 8 broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
2
20
0
1
Order By: Relevance
“…Liu et al [ 27 , 28 ] demonstrated that the use of chestnut tannins as feed additives could increase immunoglobulin levels in pigs and broilers. However, the present study did not observe changes in immunoglobulin concentrations, suggesting that the results were related to tannin type; thus far, there have been few reports describing the effect of MGM-P supplementation on immunoglobulin levels in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 27 , 28 ] demonstrated that the use of chestnut tannins as feed additives could increase immunoglobulin levels in pigs and broilers. However, the present study did not observe changes in immunoglobulin concentrations, suggesting that the results were related to tannin type; thus far, there have been few reports describing the effect of MGM-P supplementation on immunoglobulin levels in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Among described alternatives, phytochemicals and tannins in particular, are probably some of the most promising candidates since many studies assessed animal responses to the dietary inclusion of these compounds [7, 27,28] and some of the reported biological activities are similar to those proposed for AGPs [5,6]. Although the beneficial effects of phytochemicals as feed additives in poultry have been previously described [8, [29][30][31], and different tannin-based products have been used in commercial operations for many years now [5,14], descriptions on their application as main component of an AGP free . CC-BY 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…Among described alternatives, phytochemicals and tannins in particular, are probably some of the most promising candidates since many studies assessed animal responses to the dietary inclusion of these compounds [7,27,28] and some of the reported biological activities are similar to those proposed for AGPs [5,6]. Although the beneficial effects of phytochemicals as feed additives in poultry have been previously described [8,[29][30][31], and different tannin-based products have been used in commercial operations for many years now [5,14], descriptions on their application as main component of an AGP free program under commercial conditions are scarce [6]. In the present study, results from two different field trials show that dietary addition of a blend of chestnut and quebracho tannins at 0.1% (w/w) represents a promising alternative for AGPs, since broiler chickens raised under commercial conditions achieve similar productive results either in AGP or tannins-based programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations